Agency theory: Review of the theory and current research - Ranindya Hendrastuti; Ridoni Fardeni Harahap (Jurnal Akuntansi Aktual, 2023)
AbstractThis article intends to review the theoretical aspects and current research on agency theory. It aims to explore the main ideas, problems, and issues related to agency theory through a survey of the current literature. Agency theory is caused by agency relationships and information asymmetry which causes agency problems and agency costs. This article not only categorizes agency problems into six categories representing various concepts and problems but also solutions offered related to agency theory research over the last five years. This literature survey will enlighten practitioners and researchers in understanding, analyzing, mitigating agency problems, and guiding future research on agency theory.AbstrakArtikel ini bermaksud untuk meninjau aspek teoretis dan riset terkini tentang teori keagenan. Hal ini bertujuan untuk mengeksplorasi ide-ide utama, masalah, dan isu-isu yang terkait dengan teori keagenan melalui survei literatur saat ini. Teori keagenan disebabkan oleh hubungan keagenan dan asimetri informasi yang menyebabkan masalah keagenan dan biaya keagenan. Artikel ini tidak hanya mengkategorikan masalah keagenan ke dalam enam kategori yang mewakili berbagai konsep dan masalah tetapi juga menawarkan solusi terkait dengan riset teori keagenan selama lima tahun terakhir. Survei literatur ini akan mencerahkan praktisi dan peneliti dalam memahami, menganalisis, mengurangi masalah keagenan, dan membantu memandu riset selanjutnya tentang teori keagenan.